2021
DOI: 10.52836/sayistay.966483
|View full text |Cite
|
Sign up to set email alerts
|

Türki̇ye’de Yatirim Teşvi̇kleri̇ni̇n Bölgesel Ekonomi̇k Büyüme Üzeri̇ndeki̇ Etki̇si̇: Ampi̇ri̇k Bi̇r Anali̇z

Abstract: Regional inequalities continue to be a major barrier preventing economic growth and development, especially for developing countries. Governments' efforts to use public investment incentives in eliminating regional inequalities are among the most frequently implemented policies. From this point of view, this paper examines the impact of regional public investment incentives on regional economic growth in 26 development regions of Turkey over the 2004-2018 period using panel data analysis. The results of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…They found a significant impact of incentives on the economic development of most regions. They concluded that the findings reveal government concern and commitment toward covering up regional disparities through targeted financial support (Sagdich, Karash, Yildiz, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…They found a significant impact of incentives on the economic development of most regions. They concluded that the findings reveal government concern and commitment toward covering up regional disparities through targeted financial support (Sagdich, Karash, Yildiz, 2021).…”
Section: Introductionmentioning
confidence: 99%